2012
DOI: 10.1038/nchem.1243
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the chemical beauty of drugs

Abstract: Druglikeness is a key consideration when selecting compounds during the early stages of drug discovery. However, evaluation of druglikeness in absolute terms does not adequately reflect the whole spectrum of compound quality. More worryingly, widely used rules may inadvertently foster undesirable molecular property inflation as they permit the encroachment of rule-compliant compounds toward their boundaries. We propose a measure of druglikeness based on the concept of desirability called Quantitative Estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1,389
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,613 publications
(1,401 citation statements)
references
References 46 publications
5
1,389
0
7
Order By: Relevance
“…7,12,13,14,15 The median and mean molecular weight of approved drugs has risen by only around 50Da (15%) over the past 3 decades, whilst the median and mean molecular weight of synthesized experimental compounds has risen by over 100Da (30%). 16 In contrast, the molecules being published in the literature, 15 and patented by the pharmaceutical industry, 17 as well as those entering clinical development pipelines, 10 are more lipophilic, larger, and less three-dimensional 14,18 than approved oral drugs. Yet, compounds with higher molecular weight and higher lipophilicity face a higher probability of failure at each stage of clinical development.…”
Section: Introductionmentioning
confidence: 97%
“…7,12,13,14,15 The median and mean molecular weight of approved drugs has risen by only around 50Da (15%) over the past 3 decades, whilst the median and mean molecular weight of synthesized experimental compounds has risen by over 100Da (30%). 16 In contrast, the molecules being published in the literature, 15 and patented by the pharmaceutical industry, 17 as well as those entering clinical development pipelines, 10 are more lipophilic, larger, and less three-dimensional 14,18 than approved oral drugs. Yet, compounds with higher molecular weight and higher lipophilicity face a higher probability of failure at each stage of clinical development.…”
Section: Introductionmentioning
confidence: 97%
“…The mechanisms of uptake of gallium corroles, and macrocyclic compounds in general, into cancer cells remain elusive, and factors that control cell permeability are mostly unknown (5, 7). Recent research in drug discovery and development (7) has focused on altering the physical and chemical properties of macrocycles in attempts to improve cell permeability (5,53). Some chemical properties that have been shown to enhance cell permeability and uptake include lower molecular weight (M r ), smaller polar surface area (tPSA), and higher calculated lipophilicity (cLogP) (5).…”
Section: Significancementioning
confidence: 99%
“…In tests against expert medicinal chemists it performed as well as the best human experts inside Pfizer. The method has similarities to the subsequent QED method published by Hopkins et al 50 Analysis of the screening file with the MCA algorithm, after the elimination of both the redundant and the potentially reactive and toxic molecules, revealed a small but significant fraction of the file as unattractive and less likely to be followed up as hits for oral therapeutic targets. Closer inspection of this section of the file revealed that such compounds fall into a number of areas of chemical space, including compounds with known activity against specific targets.…”
Section: Attractiveness and Tiering Of The Filementioning
confidence: 99%